Independența instituției ombudsmanului, condiție indispensabilă a statului de drept și acces la valorile europene - Zubco, Alexandru (CEP USM, 2024)
The institution of the Ombudsman plays an important role in strengthening democracy, the rule of law, good administration, the protection and promotion of fundamental human rights and freedoms. It is the duty of the state to support and protect in this way, the Institution of the People's Advocate and to refrain from any action that undermines its independence. The competence of the Ombudsman regarding judicial or administrative authorities should be limited to ensuring the procedural efficiency and administrative functioning of this system. The People's Advocate will not be involved in the judicial system, for example, but will be able to monitor and report on the level of respect for the constitutionally guaranteed right to a fair trial. The ombudsman will not be able to annul an administrative act, but he will be able to support whether or not it contravenes international human rights standards. The ombudsman will not be able to hold civil servants accountable, but through his reports he will be able to reiterate the degree of respect for human rights by the public/administrative institution or any other entity.Obviously, in his mandate, the Ombudsman will not get involved in political, administrative or professional activities incompatible with his independence and impartiality. In this paper, the authors will analyze the level of compliance with the above-mentioned guarantees by the state authorities in the context of precedents from the Republic of Moldova and other states and how effective they are or can be in a state in democratic transition.

Instituția Ombudsmanului joacă un rol important la întărirea democrației, principiului statului de drept, buna administrare, protecția și promovarea drepturilor și libertăților fundamentale ale omului. Îndatorirea statului este să suporte și protejeze pe această cale, Instituția Avocatului Poporului și să se abțină de la orice acțiune care subminează independența sa. Competența Ombudsmanului ce ține de autoritățile judiciare sau administrative ar trebui limitată la asigurarea eficienței procedurale și funcționării administrative ale acestui sistem. Avocatul Poporului nu se va implica în sistemul judecătoresc spre exemplu, însă, va putea monitoriza și expune asupra nivelului de respectare a dreptului la un proces echitabil garantat constituțional. Ombudsmanul nu va putea anula un act administrativ, însă va putea susține dacă acesta contravine sau nu standardelor internaționale privind drepturile omului. Ombudsmanul nu va putea atrage la răspundere funcționarii publici, însă prin rapoartele sale va putea reitera despre gradul de respectare a drepturilor omului de instituția publică administrativă sau orice altă entitate. Evident că în mandatul său, Ombudsmanul nu se va implica în activități politice, administrative sau profesionale incompatibile cu independența și imparțialitatea sa. n prezenta lucrare, autorii vor analiza asupra nivelului de respectare a garanțiilor sus-expuse de autoritățile statele în contextul unor precedente din Republica Moldova și alte stat și cât de eficiente sunt sau pot fi acestea într-un stat în tranziție democratică.
Independence of the ombudsman institution, an indispensable condition of the rule of law and access to european values
Keywords: The People's Advocate; Ombudsman; international human rights standards; human rights; democracy; obligations of public authorities; Office of the People's Advocate; independence; impartiality; interference; Avocatul Poporului; Ombudsmanul; standarde internaționale privind drepturile omului; drepturile omului; democrație; obligațiile autorităților publice; Oficiul Avocatului Poporului; independență; imparțialitate; imixtiune